Generation of endogenous pH-sensitive EGF receptor and its application in high-throughput screening for proteins involved in clathrin-mediated endocytosis - Larsen, Mads Breum; Perez Verdaguer, Mireia; Schmidt, Brigitte F; Bruchez, Marcel P; Watkins, Simon C; Sorkin, Alexander (eLife, 2019)
Previously we used gene-editing to label endogenous EGF receptor (EGFR) with GFP and demonstrate that picomolar concentrations of EGFR ligand drive signaling and endocytosis of EGFR in tumors in vivo (Pinilla-Macua et al., 2017). We now use gene-editing to insert a fluorogen activating protein (FAP) in the EGFR extracellular domain. Binding of the tandem dye pair MG-Bis-SA to FAP-EGFR provides a ratiometric pH-sensitive model with dual fluorescence excitation and a single far-red emission. The excitation ratio of fluorescence intensities was demonstrated to faithfully report the fraction of FAP-EGFR located in acidic endosomal/lysosomal compartments. Coupling native FAP-EGFR expression with the high method sensitivity has allowed development of a high-throughput assay to measure the rates of clathrin-mediated FAP-EGFR endocytosis stimulated with physiological EGF concentrations. The assay was utilized to screen a phosphatase siRNA library. These studies highlight the utility of endogenous pH-sensitive FAP-receptor chimeras in high-throughput analysis of endocytosis.
Keywords: EGF receptor; endocytosis; RNAi